Percepções dos processos e meios de teleatendimento de terapia ocupacional junto a indivíduos adultos com disfunções físicas em isolamento social - Souza, Flávia Fernanda dos Santos de (Universidade Federal de São Carlos, 2023)
Due to the emergence of COVID-19, which impacted Brazil, there was a need for social isolation as one of the main measures to combat the SARS-CoV-2 virus. Consequently, all non-essential services had to be closed, including some healthcare services. As a result, various patients with physical dysfunctions were unable to receive occupational therapy treatment, becoming more vulnerable to health complications, as well as facing new challenges arising from the isolation. Objective: To assess the perceptions of users with traumatic orthopedic injuries participating in the extension project "Health Education and Occupational Therapy Guidance for Patients with Physical Dysfunctions during the COVID-19 Pandemic Isolation Period" regarding the process of telehealth occupational therapy (teleconsultation and telemonitoring) at a university health school in a Federal University in the interior of the state of São Paulo, Brazil. Methodology: This is a retrospective, exploratory, qualitative study that used a characterization form to define the research population, along with an open questionnaire administered through Google Forms to the 11 research participants. Research Results: The categories identified were: social isolation, remote care, support, and guidance materials. The respective subcategories were: changes, overall health status; differences in healthcare and well-being; support; healthcare demands; difficulties; social isolation. The thematic units related to the categories and subcategories were: effects; rehabilitation changes; symptom improvement; emotional well-being enhancement; adaptation to the new mode of care; telehealth; positive experiences; challenges; symptom control and difficulties. Final Remarks: The results indicated that despite the challenges presented by telehealth in occupational therapy, the patients' perceptions were positive, highlighting an improvement in their overall health and quality of life.
Perceptions of occupational therapy telehealth processes and methods among adults with physical disabilities in social isolation
Keywords: COVID-19; Pandemia; Isolamento social; Disfunção física; Terapia ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL